Population genetic structure in Plantago ovata var. decumbens with using ISSR markers - Mohsenzadeh Saeed (Genetika, 2019)
Plantago ovata (Plantaginaceae) is a medicinal plant cultivated extensively in Western Asia for seed husk known as blonde Psyllium or Isabgol. We used ISSR molecular markers to investigate the population genetic structure and genetic divergence within P. ovata populations. We identified P. ovata variety as var. decumbens based on the morphological data. WARD tree and PCoA plot produced similar results on morphological data. AMOVA revealed a significant genetic differentiation among the studied populations. STRUCTURE analyses showed some degree of gene flow among the studied populations. NJ tree and PCoA plot of ISSR data revealed that there are at least three genetic groups within the studied populations. Though the studied populations in P. ovata are genetically differentiated, there are not qualitative morphological features for differentiating among theirs. Therefore, we consider them as ecotypes within P. ovata.